The New and Old Europe: East-West Split in Pharmaceutical Spending - Jakovljevic, Mihajlo; Lazarevic, Marija; Milovanovic, Olivera; Kanjevac, Tatjana (Frontiers in Pharmacology, 2016)
HIGHLIGHTS Since the geopolitical developments of 1989, former centrally planned economies of Eastern Europe followed distinctively different pathways in national pharmaceutical expenditure evolution as compared to their free market Western European counterparts. Long term spending on pharmaceuticals expressed as percentage of total health expenditure was falling in free market economies as of 1989. Back in early 1990s it was at higher levels in transitional Eastern European countries and actually continued to grow further. Public financing share of total pharmaceutical expenditure was steadily falling in most Central and Eastern European countries over the recent few decades. Opposed scenario were EU-15 countries which successfully increased their public funding of prescription medicines for the sake of their citizens. Pace of annual increase in per capita spending on medicines in PPP terms, was at least 20% faster in Eastern Europe compared to their Western counterparts. During the same years, CEE region was expanding their pharmaceuticals share of health spending in eight fold faster annual rate compared to the EU 15. Private and out-of-pocket expenditure became dominant in former socialist countries. Affordability issues coupled with growing income inequality in transitional economies will present a serious challenge to equitable provision and sustainable financing of pharmaceuticals in the long run.